Establishing the clinical utility of epigenetic markers in cancer: many challenges ahead. (October 2013) - Zarzour, Peter; Hesson, Luke B; Ward, Robyn L
The use of epigenetic biomarkers in cancer management relies on the availability of robust assays and evidence that these markers are able to segregate clinically significant groups of patients. While many cancers are characterized by genetic and epigenetic modifications, it is far simpler to develop molecular tests that detect genetic rather than epigenetic changes. In this special report, we will describe the challenges associated with developing epigenetic assays and the practical issues that must be overcome before they can be used in the clinic.